1994
DOI: 10.1200/jco.1994.12.6.1177
|View full text |Cite
|
Sign up to set email alerts
|

Myeloablative therapy with autologous bone marrow transplantation as consolidation therapy for recurrent follicular lymphoma.

Abstract: These results are encouraging, although preliminary; it remains to be established whether this treatment prolongs survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(95 citation statements)
references
References 33 publications
3
90
2
Order By: Relevance
“…[1][2][3] Mobilized peripheral-blood progenitor-cells (PBPC) have largely replaced autologous bone marrow (BM) as the stem-cell source, mainly due to the noninvasive collection technique and a faster engraftment after PBPC transplantation. 4 Prior chemotherapy, number of CD34 þ cells infused, and administration of hematopoietic growth factors influence hematologic recovery.…”
Section: Beam; Cd34 þ Cellsmentioning
confidence: 99%
“…[1][2][3] Mobilized peripheral-blood progenitor-cells (PBPC) have largely replaced autologous bone marrow (BM) as the stem-cell source, mainly due to the noninvasive collection technique and a faster engraftment after PBPC transplantation. 4 Prior chemotherapy, number of CD34 þ cells infused, and administration of hematopoietic growth factors influence hematologic recovery.…”
Section: Beam; Cd34 þ Cellsmentioning
confidence: 99%
“…2 The role of such treatment intensification in the histologically indolent lymphomas is less clear and results from randomised controlled trials have not yet been reported. However, several non-randomised studies have suggested prolonged disease-free survival in patients with histologically indolent NHL who have received high-dose therapy with stem cell support, [3][4][5][6] and such treatment intensification is increasingly used in younger patients.…”
mentioning
confidence: 99%
“…[1][2][3][4] However, the value of such therapy in patients with low-grade lymphoma is less well established. 5 Issues such as the optimal timing of therapy, [5][6][7] the value of purging, [7][8][9] and the relative merit of autologous stem cells vs allogeneic stem cells 10 remain unresolved. Since some patients with low-grade NHL may experience prolonged survival, even with limited initial therapy such as 'watchful waiting', it is difficult to establish that high-dose therapy has an impact on the survival of patients with low-grade NHL.…”
mentioning
confidence: 99%